Penerapan Strategi Ekonomi Sirkular pada UMKM Katering di Kecamatan Medan Johor: Solusi untuk Pengurangan Limbah Makanan dan Peningkatan Keberlanjutan Bisnis - Yusrita, Yusrita; Pangestu, Angga; Farizal, Ryan (Fakultas Ekonomi, 2025)
Catering SMEs play a crucial role in supporting the national economy, particularly in the culinary sector. However, this sector faces environmental challenges, especially in waste management and resource efficiency. The concept of a circular economy offers an effective solution to address these challenges by extending product life cycles and reducing waste. This study aims to analyze the implementation of circular economy practices in catering SMEs in Medan Johor District. The method used is a case study with data collection through interviews, observations, and document analysis. The results show that most SMEs have adopted environmentally friendly measures such as the use of sustainable raw materials and organic waste composting. However, challenges such as limited capital and knowledge remain significant obstacles. Government policy support and collaboration with private entities can accelerate the implementation of a circular economy in this sector